Biochemical and immunological heterogeneity of the Ro ribonucleoprotein particles. Analysis with sera specific for the RohY5 particle. - Boire, G (J Clin Invest, 1989)
Anti-Ro autoantibodies found in sera from patients with systemic lupus erythematosus and related diseases precipitate four RNAs (hY1-hY5) from human cell extracts. We identified two patient sera that selectively immunoprecipitated from such extracts the Ro particle containing the hY5 RNA (RohY5 particle). Using cell fractions either enriched in or depleted of RohY5 particles, we have shown that these sera contain autoantibodies that target an antigenic determinant on the 60-kD Ro polypeptide that is expressed only on RohY5 particles and is absent on the Ro particles containing the hY1-hY4 RNAs (RohY1-hY4 particles). In a competitive inhibition assay using a cell fraction enriched in RohY1-hY4 particles but depleted of RohY5 particles, four of six control anti-Ro sera were also shown to contain antibodies reactive with the epitope specific for the RohY5 particle. Thus anti-RohY5 antibodies frequently occur in tandem with anti-Ro antibodies, but are not detected unless inhibition assays are performed. Finally, anti-RohY5 specific sera do not immunoprecipitate any Ro particles from various nonhuman cell lines. In contrast to other autoantibodies in systemic lupus and related diseases that bind conserved regions on conserved polypeptides, this observation suggests that a portion of the anti-Ro response targets a nonconserved epitope on a conserved autoantigen. IMAGES: